Integration of Kupffer cells into human iPSC-derived liver organoids for modeling liver dysfunction in sepsis - Yang Li; Yunzhong Nie; Xia Yang; Yang Liu; Xiaoshan Deng; Yoshihito Hayashi; Riana Plummer; Qinglin Li; Na Luo; Toshiharu Kasai; Takashi Okumura; Yu Kamishibahara; et al. (Cell Reports, 2024)
Summary: Maximizing the potential of human liver organoids (LOs) for modeling human septic liver requires the integration of innate immune cells, particularly resident macrophage Kupffer cells. In this study, we present a strategy to generate LOs containing Kupffer cells (KuLOs) by recapitulating fetal liver hematopoiesis using human induced pluripotent stem cell (hiPSC)-derived erythro-myeloid progenitors (EMPs), the origin of tissue-resident macrophages, and hiPSC-derived LOs. Remarkably, LOs actively promote EMP hematopoiesis toward myeloid and erythroid lineages. Moreover, supplementing with macrophage colony-stimulating factor (M-CSF) proves crucial in sustaining the hematopoietic population during the establishment of KuLOs. Exposing KuLOs to sepsis-like endotoxins leads to significant organoid dysfunction that closely resembles the pathological characteristics of the human septic liver. Furthermore, we observe a notable functional recovery in KuLOs upon endotoxin elimination, which is accelerated by using Toll-like receptor-4-directed endotoxin antagonist. Our study represents a comprehensive framework for integrating hematopoietic cells into organoids, facilitating in-depth investigations into inflammation-mediated liver pathologies.